Finding Nemo [videorecording (DVD)] (Buena Vista Home Entertainment, 2013)
In the depths of the Great Barrier Reef, Marlin, an overly protective clownfish, embarks on a daring rescue mission when his beloved son, Nemo, gets scooped up by a diver. With his unforgettable friend Dory by his side, Marlin encounters an ocean full of memorable comedic characters on his momentous journey to find Nemo.